2006
DOI: 10.1021/la062470y
|View full text |Cite
|
Sign up to set email alerts
|

Templating Behavior of a Long-Chain Ionic Liquid in the Hydrothermal Synthesis of Mesoporous Silica

Abstract: The long-chain ionic liquid (IL) 1-hexadecyl-3-methylimidazolium chloride (C(16)mimCl) was used as a template to prepare porous silica with a two-dimensional hexagonal p6mm mesopore structure (MCM-41-type) as well as with a cubic Ia3d (gyroid, MCM-48-type structure) framework in basic synthesis medium via a hydrothermal synthesis procedure. A systematic study was carried out addressing the influence of the relative concentration of the IL and the pH on the mesostructure. As a main result, the IL template shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 50 publications
5
125
0
Order By: Relevance
“…ILs have also been widely explored as potential ionic surfactants with different areas and applications such as extraction of organic compounds, metal ions and radioactive isotopes [55][56], as template to produce micro/mesoporous materials [57][58], in microemulsion [59][60][61]. The surfactant properties of ILs are easily understood if we consider that these compounds generally have a well-defined structure with hydrophilic character and another with hydrophobic character, i.e.…”
Section: Ionic Liquids As Surfactantsmentioning
confidence: 99%
“…ILs have also been widely explored as potential ionic surfactants with different areas and applications such as extraction of organic compounds, metal ions and radioactive isotopes [55][56], as template to produce micro/mesoporous materials [57][58], in microemulsion [59][60][61]. The surfactant properties of ILs are easily understood if we consider that these compounds generally have a well-defined structure with hydrophilic character and another with hydrophobic character, i.e.…”
Section: Ionic Liquids As Surfactantsmentioning
confidence: 99%
“…Long chain imidazolium ILs are of particular interest due to its tendency to self-assemble which is preferred in developing ordered mesoporous materials [30]. A series of 1-alkyl-3-methylimidazolium chloride (C n MimCl where n = 10, 14, 16 and 18) were used to prepare highly ordered lamellar silica via nanocasting technique and the developed silica exhibited microporosity [31].…”
Section: Introductionmentioning
confidence: 99%
“…A series of 1-alkyl-3-methylimidazolium chloride (C n MimCl where n = 10, 14, 16 and 18) were used to prepare highly ordered lamellar silica via nanocasting technique and the developed silica exhibited microporosity [31]. Wang et al used 1-hexadecyl-3-methylimidazolium chloride to develop ordered mesoporous silica, MCM-41 and MCM-48 via hydrothermal method [30]. Development of mesoporous silica is not limited to long chain imidazolium based ILs.…”
Section: Introductionmentioning
confidence: 99%
“…The current work focuses on the question whether [Bmim] [FeCl 4 ] can act as an ILP for the synthesis of a transition metal containing mesoporous silica material. It has also been demonstrated that ILs are efficient tools for the design of mesoporous silica [22] [23] [24] [25] [26]. As a result, we wondered if a suitable IL may (i) catalyze the hydrolysis of appropriate silanes to form a mesoporous matrix and (ii) at the same time serve as the metal source for the formation of catalytically active metal species within the SiO 2 network.…”
Section: Introductionmentioning
confidence: 99%